2018
DOI: 10.1177/0022034518756330
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin and the Initiation and Progression of Head and Neck Cancer

Abstract: Calprotectin (S100A8/A9), a heterodimeric complex of calcium-binding proteins S100A8 and S100A9, is encoded by genes mapping to the chromosomal locus 1q21.3 of the epidermal differentiation complex. Whereas extracellular calprotectin shows proinflammatory and antimicrobial properties by signaling through RAGE and TLR4, intracytoplasmic S100A8/A9 appears to be important for cellular development, maintenance, and survival. S100A8/A9 is constitutively expressed in myeloid cells and the stratified mucosal epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 96 publications
2
30
0
Order By: Relevance
“…As for S100A8, we did not detect a correlation between lymphatic metastasis and the expression in SCC cells and stromal cells. In contrast to LOX, MT1-MMP, and TIMP-1, declining expression of S100A8 in head and neck primary SCC indicated worse prognosis (Argyris et al, 2018;Khammanivong et al, 2016). Argyris et al showed that S100A8/A9 complex (calprotectin) downregulated MMP-2 expression, which inhibited invasion and migration of cancer cells in vitro (Argyris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for S100A8, we did not detect a correlation between lymphatic metastasis and the expression in SCC cells and stromal cells. In contrast to LOX, MT1-MMP, and TIMP-1, declining expression of S100A8 in head and neck primary SCC indicated worse prognosis (Argyris et al, 2018;Khammanivong et al, 2016). Argyris et al showed that S100A8/A9 complex (calprotectin) downregulated MMP-2 expression, which inhibited invasion and migration of cancer cells in vitro (Argyris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to LOX, MT1-MMP, and TIMP-1, declining expression of S100A8 in head and neck primary SCC indicated worse prognosis (Argyris et al, 2018;Khammanivong et al, 2016). Argyris et al showed that S100A8/A9 complex (calprotectin) downregulated MMP-2 expression, which inhibited invasion and migration of cancer cells in vitro (Argyris et al, 2018). Conversely, Choi et al demonstrated that overexpression of S100A8 and S100A9 increased tumor growth and volume in cutaneous SCC (Choi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to anaplastic thyroid carcinoma, it has no significant role in non-neoplastic thyroid tissue and well-differentiated thyroid tumors. 35 And as an important proinflammatory factor, platelets have also been studied as a biomarker. It will be rather convenient if the platelets could be the marker, since the test of it is such regular.…”
Section: Tumor-related Markersmentioning
confidence: 99%
“…In addition to anaplastic thyroid carcinoma, it has no significant role in non-neoplastic thyroid tissue and well-differentiated thyroid tumors. 35 …”
Section: Blood Markersmentioning
confidence: 99%